Does intraocular straylight predict night driving visual performance? Correlations between straylight levels and contrast sensitivity, halo size, and hazard recognition distance with and without glare - Ungewiss, Judith; Schiefer, Ulrich; Eichinger, Peter; Wörner, Michael; Crabb, David P.; Jones, Pete R. (Frontiers in Human Neuroscience, 2022)
Purpose: To evaluate the relationship between intraocular straylight perception and: (i) contrast sensitivity (CS), (ii) halo size, and (iii) hazard recognition distance, in the presence and absence of glare. Subjects and methods: Participants were fifteen (five female) ophthalmologically healthy adults, aged 54.6 to 80.6 (median: 67.2) years. Intraocular straylight (log s) was measured using a straylight meter (C-Quant; Oculus GmbH, Wetzlar/Germany). CS with glare was measured clinically using the Optovist I device (Vistec Inc., Olching/FRG) and also within a driving simulator using Landolt Cs. These were presented under both static or dynamic viewing conditions, and either with or without glare. Hazard detection distance was measured for simulated obstacles of varying contrast. For this, the participant was required to maintain a speed of 60 km/h within a custom-built nighttime driving simulator. Glare was simulated by LED arrays, moved by cable robots to mimic an oncoming car’s headlights. Halo size (“halometry”) was measured by moving Landolt Cs outwards originating from the center of a static glare source. The outcome measure from “halometry” was the radius of the halo (angular extent, in degrees visual angle). Results: The correlation between intraocular straylight perception, log s, and hazard recognition distance under glare was poor for the low contrast obstacles (leading/subdominant eye: r = 0.27/r = 0.34). Conversely, log CS measured with glare strongly predicted hazard recognition distances under glare. This was true both when log CS was measured using a clinical device (Optovist I: r = 0.93) and within the driving simulator, under static (r = 0.69) and dynamic (r = 0.61) conditions, and also with "halometry” (r = 0.70). Glare reduced log CS and hazard recognition distance for almost all visual function parameters. Conclusion: Intraocular straylight was a poor predictor of visual function and driving performance within this experiment. Conversely, CS was a strong predictor of both hazard recognition and halo extent. The presence of glare and motion lead to a degradation of CS in a driving simulator. Future studies are necessary to evaluate the effectiveness of all above-mentioned vision-related parameters for predicting fitness to drive under real-life conditions.